Analysis of temporal and spatial variation of visibility in Beijing, China, from 2015 to 2020 - Lingling Shen; Xuebo Fan; Xiya Zhang (Natural Hazards Research, 2023)
This study analyzes the visibility characteristics in Beijing from 2015 to 2020 using the 10-min average horizonal visibility hourly data from 20 national meteorological stations (NMSs). We examine the visibility trends on different time and space scales, including year, month, day. Our findings reveal that the visibility of the Beijing area shows a noticeable change trend year by year. Overall, the number of days with high visibility (visibility ≥10 ​km) has increased, and the number of hours with low visibility (visibility < 1 ​km) has decreased. Low visibility in Beijing mainly occurs during winter, whereas high visibility occurs throughout the year. On a daily scale, low visibility mainly occurs around 6 a.m. and 8 p.m. Furthermore, the spatial distribution of high and low visibility in Beijing correlates with the topographic boundary between plains and mountains. We observed that mountainous areas have more days with increased visibility and fewer hours with low visibility, while plain areas have fewer days with high visibility and more hours with high visibility. These findings have implications for understanding the environmental hazards caused by poor visibility in Beijing, such as impaired air quality, increased traffic accidents, and reduced human mobility. By identifying the temporal and spatial patterns of visibility, this study provides valuable information that can be used to improve hazard mitigation strategies and promote public safety.